2008
DOI: 10.1210/jc.2008-1280
|View full text |Cite
|
Sign up to set email alerts
|

High-Circulating Leptin Levels Are Associated with Greater Risk of Hypertension in Men Independently of Body Mass and Insulin Resistance: Results of an Eight-Year Follow-Up Study

Abstract: In this sample of originally normotensive men, circulating LPT level was a significant predictor of the risk to develop HPT over 8 yr, independently of BMI and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 42 publications
4
53
1
3
Order By: Relevance
“…27 However, in the current study, the association between leptin and hypertension was present even among subjects with normal weight (BMI Ͻ25 kg/m 2 ), suggesting the involvement of mechanisms other than obesity, such as inflammation, as a potential explanation for the observed association. Furthermore, our findings are consistent with the findings by Galletti et al, 3 who reported an association between plasma leptin levels and hypertension that was independent of BMI in a sample of Italian men. We also found that the association between leptin and hypertension persisted even after adjusting for high-sensitivity CRP levels, indicating that there are probably underlying explanatory mechanisms that are independent of systemic inflammation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…27 However, in the current study, the association between leptin and hypertension was present even among subjects with normal weight (BMI Ͻ25 kg/m 2 ), suggesting the involvement of mechanisms other than obesity, such as inflammation, as a potential explanation for the observed association. Furthermore, our findings are consistent with the findings by Galletti et al, 3 who reported an association between plasma leptin levels and hypertension that was independent of BMI in a sample of Italian men. We also found that the association between leptin and hypertension persisted even after adjusting for high-sensitivity CRP levels, indicating that there are probably underlying explanatory mechanisms that are independent of systemic inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies in humans, discordant results have been obtained with regard to the relationship between leptin and BP. Some investigators detected a significant association between plasma leptin levels and BP only in men, [3][4][5] others detected an association only in women, 6,7 whereas some others reported a positive relationship in both men and women. 8 -10 In the current study, we found that, although plasma leptin levels are substantially higher in women (a finding that has been consistently reported in previous literature 26 also), the leptin-hypertension association was present both in women and men.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, hyperleptinaemia promotes cardiovascular remodelling [7,8] mainly by increasing sympathetic nervous system activity [9]. Indeed, increased leptin levels may predict development of hypertension, independent of BMI and insulin resistance [10].Increasing evidence suggests that RAAS and adipose tissue are interplayers in BP regulation [11][12][13]. It has been suggested that angiotensin-converting enzyme inhibitors (ACEi) may offer advantages as monotherapy in the treatment of obese hypertensive individuals, particularly in the prevention of metabolic disorders [14].…”
mentioning
confidence: 99%